2022
DOI: 10.3390/ijerph191710843
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distributions and Intrinsic Influence Analysis of Cr, Ni, Cu, Zn, As, Cd and Pb in Sediments from the Wuliangsuhai Wetland, China

Abstract: The spatial distributions of Cr, Ni, Cu, Zn, As, Cd and Pb (potentially toxic elements, PTEs) in sediments and intrinsic influence factors from the Wuliangsuhai wetland of the Hetao Irrigation District, China were studied in this work. The results showed that excluding Zn, the total contents of other PTEs were higher than the background values, of which As (39.26 mg·kg−1) and Cd (0.44 mg·kg−1) were six-fold and seven-fold higher, respectively. Especially, the high levels of Cd (70.17%), Pb (66.53%), and Zn (57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Consequently, processes of deposition, mixing, and removal of various elements at the SWI play a pivotal role in the translocation of pollutants. Previous research using the Diffusive Gradients in Thin films (DGT) technique at the SWI has indicated that high labile Mn concentrations in the overlying water, reaching up to 22.3 mg L −1 (Yuan et al, 2018), with sediments identified as sources of heavy metals such as Pb, Zn, and Cd, particularly in the weakly mixed zone (Wang and Wang, 2017;Zhang H. et al, 2022;Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, processes of deposition, mixing, and removal of various elements at the SWI play a pivotal role in the translocation of pollutants. Previous research using the Diffusive Gradients in Thin films (DGT) technique at the SWI has indicated that high labile Mn concentrations in the overlying water, reaching up to 22.3 mg L −1 (Yuan et al, 2018), with sediments identified as sources of heavy metals such as Pb, Zn, and Cd, particularly in the weakly mixed zone (Wang and Wang, 2017;Zhang H. et al, 2022;Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…DGT has been widely employed as an in-situ passive sampling technique to assess the environmental metal chemistry at the SWI. The methodology has been extensively applied in various regions China, such as the Three Gorges Reservoir (Gao et al, 2018), in Lake Taihu (Yuan et al, 2018),in Lake Dianchi and WuliangSuhai (Wu et al, 2019;Li et al, 2022;Zhang H. et al, 2022;Zheng et al, 2022) in China. Nevertheless, limited research has been conducted on lakes in Northeast China, highlighting the need for increased focus on this geographical area.…”
Section: Introductionmentioning
confidence: 99%
“…Due to rapid economic development, many wetlands or lakes in China have become eutrophic or polluted by heavy metal [21, 22]. A Paenibacillus -like bacterium was isolated from sediment of a heavy metal polluted wetland [23], where active anaerobic ammonium oxidation and denitrifying bacteria contributed to nitrogen removal [24]. Here, we report the taxonomic characterization of a Paenibacillus -like bacterium based on a comparison of a series of phenotypic, genotypic and chemotaxonomic characteristics with other closely related type strains within the genus Paenibacillus .…”
Section: Introductionmentioning
confidence: 99%
“…The content of DNA G+C is 39–60.7 mol % [8–20]. The major respiratory quinone is menaquinone-7 (MK-7), the major cellular fatty acid is anteiso-C 15 : 0 [8–29]. The members of the genus Paenibacillus contain diphosphatidylglycerol as the major polar lipid, and some strains also contain phosphatidylethanolamine and phosphatidylglycerol [9–14, 16–20].…”
Section: Introductionmentioning
confidence: 99%